Implementasi Konsep “INature” Pada Interior Daycare Center di Surabaya - Ellysa Novia Halim; Ronald Hasudungan Irianto Sitindjak; Hendy Mulyono (Intra, 2019)
The Daycare design which is based on interaction with nature will answer the problems of daycare facilities and activity programs that does not support the establishment of character and vulnerability of early childhood’s health. The Daycare will be designed based on nature that aims to create learning experiences through interaction with nature to shape characters of the children who can be more caring with having a more fresh and healthy environment for their childhood development. The method used is a design thinking method which is devided into three processes that is inspiration, ideation, and implementation. Inspiration includes site location surveys, interviews with caregivers and parents who have toddlers, making questionnaires, and measuring rooms. Ideation includes programming analysis and schematic design stages. Implementation includes final design stages, 1: 50 presentation mock up, and presentation board.  The concept used is "INature". The designs are given colors that blend with the surrounding environment such as green, yellow, white and gray in blue as accents. INature is an abbreviation of Interact of Nature which invites children to interact and coexist with fellow children in nature-based activities. The results of the design are in the form of interior and exterior design related to the children's activity program in helping the process of character establishment during childhood.